Non-small cell lung cancer--genetic predictors - Koudelakova, Vladimira; Kneblova, Magdalena; Trojanec, Radek; Drabek, Jiri; Hajduch, Marian (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2013)
BACKGROUND: Non-small cell lung cancer (NSCLC) accounts for approximately 85% of all lung cancer that is the leading cause of cancer-related mortality worldwide. Several predictive markers have been found in NSCLC patients to date but only a few are currently used for tailored therapy. METHODS AND RESULTS: PubMed and Web of Science online databases were used to search review and original articles on the most important predictive markers in NSCLC. CONCLUSION: EGFR activating mutations (exons 18 to 21) and EML4-ALK rearrangement are clinically important markers able to select NSCLC patients which benefit from EGFR or ALK tyrosine kinase inhibitors (gefitinib, erlotinib, crizotinib). Other markers, such as KRAS mutation, EGFR T790M mutation and C-MET amplification, are responsible for resistance to these inhibitors. Overcoming of this resistance as well as discovery of new potential markers and inhibitors is the main goal of ongoing research and clinical trials in NSCLC.
Keywords: nádory plic; nemalobuněčný karcinom plic; Lung Neoplasms; Humans; inhibitory proteinkinas; Carcinoma, Non-Small-Cell Lung; ErbB Receptors; Biomarkers, Tumor; Proto-Oncogene Proteins c-met; fúzní onkogenní proteiny; ras Proteins; lidé; tyrosinkinasy; chemorezistence; protoonkogenní proteiny p21(ras); erbB receptory; protoonkogenní proteiny; Oncogene Proteins, Fusion; nádorové biomarkery; Protein Kinase Inhibitors; Protein-Tyrosine Kinases; Proto-Oncogene Proteins p21(ras); protoonkogenní proteiny c-met; Proto-Oncogene Proteins; Ras proteiny; Drug Resistance, Neoplasm